2023
DOI: 10.3390/rs15010279
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Patterns and Driving Forces of Desertification in Otindag Sandy Land, Inner Mongolia, China, in Recent 30 Years

Abstract: Desertification is one of the main obstacles to global sustainable development. Monitoring, evaluating and mastering its driving factors are very important for the prevention and control of desertification. As one of the largest deserts in China, the development of desertification in Otindag Sandy Land (OSL) resulted in the reduction in land productivity and serious ecological/environmental consequences. Although many ecological restoration projects have been carried out, the vegetation restoration of OSL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…China's desertification land covers 2.61 million km 2 , accounting for 27.20% of the total land area [8]. Serious desertification still exists in the Otindag Sandy Land [46], Tengger Desert [47], Horqin Sandy Land [48], Shiyang River basin [49], Otindag Sandy Land [50], etc.…”
Section: Desertification Dynamicmentioning
confidence: 99%
“…China's desertification land covers 2.61 million km 2 , accounting for 27.20% of the total land area [8]. Serious desertification still exists in the Otindag Sandy Land [46], Tengger Desert [47], Horqin Sandy Land [48], Shiyang River basin [49], Otindag Sandy Land [50], etc.…”
Section: Desertification Dynamicmentioning
confidence: 99%
“…Presently, employing ground-based observation stations for the long-term continuous monitoring of PM 10 has proven effective in tracking dust weather phenomena. This method is extensively utilized across various countries [14,15], regions [16,17] and cities [13,18] for predicting and monitoring dust conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…North China stands out as one of China's most densely populated regions with vigorous industrial activities and economic development. Notably, there has been an uptick in the frequency of sand and dust weather phenomena during springtime over recent years [19]. Since March 2023 alone, there have been eight signi cant episodes of such weather conditions across China-the highest count for this period in over ten years.…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [18] utilized high-resolution temporal continuous MODIS remote sensing data to focus on the dynamic changes in Horqin Sandy Land from 2000 to 2015. Various studies have demonstrated that the remote sensing index serves as an important indicator for monitoring dynamic changes in sandy lands through remote sensing [6,12,13,16,[19][20][21][22][23][24][25][26][27], and remote sensing data monitoring methods have become the primary approach for monitoring the characteristics of sandy land changes. However, owing to the influence of NDVI changes on the FVC, which is affected by meteorological conditions, there may be some randomness in the dynamic characteristics of sand changes during isolated years (such as a sudden increase in precipitation in the sand area that year, leading to a contraction in the area of sand monitored by the FVC).…”
Section: Introductionmentioning
confidence: 99%